Purification and characterisation of ,B-l,3-giucanase from trichodenna harzianum BIO 10671 - Mustafa, Muskhazli; Ramli, Salfarina; Ithnin, Nalisha; Tohfah, Nor Farizan (Universiti Putra Malaysia Press, 2005)
B-1,3-glucanase enzyme from culture filtrate of Trichoderma harzianum BIO 10671 was successively purified by precipitation with 80%acetonefollowed by anion-exchange chromatography on Neobar AQ and chromatofocusing on a Mono P HR 5/20 column. Two {3-1,3-glucanases of 32kDa and 66kDa were purified to homogeneity as judged by SDS-PAGE. The pH aptimum far the enzymes activity was pH 4-5 and maximum activity was obtained at 4YG. Enzyme activity was slightly inhibited by 20-45% in its activity by 20mM of Zn2+, Ca2+, Co2+, Mi+, Cu2+, Mn2+and Fe2+. The highest f3-1,3-glucanase hydrolysis activity was obtained on laminarin due to the similarity on f3-glucosidic bonds and followed on pustulan, glucan and cellulose, respectively.